The first prospective application of AIGS real-time fluorescence PCR in precise diagnosis and treatment of meningioma: Case report - Han, Zhe; Chi, Huizhong; Li, Xueen; Jia, Deze; Li, Haiyan; Ni, Shilei; Zhang, Kailiang; Feng, Zichao; Wang, Qingtong; Xue, Hao; Li, Gang (Frontiers in Neuroscience, 2023)
Background: The emergence of the new WHO classification standard in 2021 incorporated molecular characteristics into the diagnosis system for meningiomas, making the diagnosis and treatment of meningiomas enter the molecular era. Recent Findings: At present, there are still some problems in the clinical molecular detection of meningioma, such as low attention, excessive detection, and a long cycle. In order to solve these clinical problems, we realized the intraoperative molecular diagnosis of meningioma by combining real-time fluorescence PCR and AIGS, which is also the first known product applied to the intraoperative molecular diagnosis of meningioma. Implications for Practice: We applied AIGS to detect and track a patient with TERTp mutant meningioma, summarized the process of intraoperative molecular diagnosis, and expounded the significance of intraoperative molecular diagnosis under the new classification standard, hoping to optimize the clinical decision-making of meningioma through the diagnosis and treatment plan of this case.